Efeito do plasma rico em plaquetas e da fibrina rica em plaquetas na cicatrização de feridas cutâneas em ratos - Camargo, Fernanda Ferreira de (2013)
Objective: To evaluate the effect of platelet-rich plasma (PRP) and platelet-rich fibrin (PRF) on cutaneous wound healing in rats by comparing treated and control wounds. Material and Methods: Forty-eight Wistar rats were used in the study. Two wounds with 1-cm diameter, of total skin thickness, were excised from the back of the animals and treated with either PRP or PRF and saline (paired model). The wounds were evaluated immediately after the procedure and after 7 and 14 days using macroscopic (photographs) and microscopic (histology) methods. The photographs were used to measure the area of wounds in order to analyse wound contraction (morphometric analysis). The histological images permitted a count-analysis of collagen concentration (histomorphometric analysis) while the histological slides providet the description of the wounds characteristics. Results: Morphometric analysis revealed statistically significant time effect (P<0.001) and treatment group effect (P=0.022) over the observation period. The rate of wound contraction was higher in PRF-treated wounds than in PRP-treated wounds (P=0.030). In the histomorphometric analysis, mean collagen concentration, on the images of the experimental groups, increased significantly (P<0.001) from day 7 to day 14. There was wide variation in the percentage of collagen concentration: 129% in the PRF group vs. 22% in the PRP group; however, this difference did not achieve statistical significance (P=0.380). Histology of the wounds suggested a more accelerated healing process in the PRF group vs. the PRP group, despite the lack of statistical significance in the characteristics analyzed. PRP-treated and PRF-treated groups were not statistically superior to their controls in any of the studied variables. Conclusion: The present results suggest that treatment with PRP and PRF were not more effective than saline for cutaneous wound healing in rats. However, PRF proved to be superior to PRP.